Grounding Soil Carbon Sequestration Claims: The Role of Long‐Term EC Flux Data - Elaine Mitchell; David Rowlings; Jonathan Sanderman (Global Change Biology, 2025)

Marsh sediments chronically exposed to nitrogen enrichment contain degraded organic matter that is less vulnerable to decomposition via nitrate reduction - Ashley N. Bulseco; Anna E. Murphy; Anne E. Giblin; Jane Tucker; Jonathan Sanderman; Jennifer L. Bowen (Science of The Total Environment, 2024)

Potential of globally distributed topsoil mid-infrared spectral library for organic carbon estimation - Yongsheng Hong; Jonathan Sanderman; Tomislav Hengl; Songchao Chen; Nan Wang; Jie Xue; Zhiqing Zhuo; Jie Peng; Shuo Li; Yiyun Chen; Yaolin Liu; Abdul Mounem Mouazen; et al. (CATENA, 2024)

The Coastal Carbon Library and Atlas: Open source soil data and tools supporting blue carbon research and policy - James R. Holmquist; David Klinges; Michael Lonneman; Jaxine Wolfe; Brandon Boyd; Meagan Eagle; Jonathan Sanderman; Kathe Todd‐Brown; E. Fay Belshe; Lauren N. Brown; Samantha Chapman; Ron Corstanje; et al. (Global Change Biology, 2024)
Quantifying carbon fluxes into and out of coastal soils is critical to meeting greenhouse gas reduction and coastal resiliency goals. Numerous ‘blue carbon’ studies have generated, or benefitted from, synthetic datasets. However, the community those efforts inspired does not have a centralized, standardized database of disaggregated data used to estimate carbon stocks and fluxes. In this paper, we describe a data structure designed to standardize data reporting, maximize reuse, and maintain a chain of credit from synthesis to original source. We introduce version 1.0.0. of the Coastal Carbon Library, a global database of 6723 soil profiles representing blue carbon‐storing systems including marshes, mangroves, tidal freshwater forests, and seagrasses. We also present the Coastal Carbon Atlas, an R‐shiny application that can be used to visualize, query, and download portions of the Coastal Carbon Library. The majority (4815) of entries in the database can be used for carbon stock assessments without the need for interpolating missing soil variables, 533 are available for estimating carbon burial rate, and 326 are useful for fitting dynamic soil formation models. Organic matter density significantly varied by habitat with tidal freshwater forests having the highest density, and seagrasses having the lowest. Future work could involve expansion of the synthesis to include more deep stock assessments, increasing the representation of data outside of the U.S., and increasing the amount of data available for mangroves and seagrasses, especially carbon burial rate data. We present proposed best practices for blue carbon data including an emphasis on disaggregation, data publication, dataset documentation, and use of standardized vocabulary and templates whenever appropriate. To conclude, the Coastal Carbon Library and Atlas serve as a general example of a grassroots F.A.I.R. (Findable, Accessible, Interoperable, and Reusable) data effort demonstrating how data producers can coordinate to develop tools relevant to policy and decision‐making.

Molecular complexity and diversity of persistent soil organic matter - Andrew R. Jones; Ram C. Dalal; Vadakattu V.S.R. Gupta; Susanne Schmidt; Diane E. Allen; Geraldine E. Jacobsen; Michael Bird; A. Stuart Grandy; Jonathan Sanderman (Soil Biology and Biochemistry, 2023)

Land‐based measures to mitigate climate change: Potential and feasibility by country - Stephanie Roe; Charlotte Streck; Robert Beach; Jonah Busch; Melissa Chapman; Vassilis Daioglou; Andre Deppermann; Jonathan Doelman; Jeremy Emmet‐Booth; Jens Engelmann; Oliver Fricko; Chad Frischmann; et al. (Global Change Biology, 2021)
Land‐based climate mitigation measures have gained significant attention and importance in public and private sector climate policies. Building on previous studies, we refine and update the mitigation potentials for 20 land‐based measures in >200 countries and five regions, comparing “bottom‐up” sectoral estimates with integrated assessment models (IAMs). We also assess implementation feasibility at the country level. Cost‐effective (available up to $100/tCO 2 eq) land‐based mitigation is 8–13.8 GtCO 2 eq yr −1 between 2020 and 2050, with the bottom end of this range representing the IAM median and the upper end representing the sectoral estimate. The cost‐effective sectoral estimate is about 40% of available technical potential and is in line with achieving a 1.5°C pathway in 2050. Compared to technical potentials, cost‐effective estimates represent a more realistic and actionable target for policy. The cost‐effective potential is approximately 50% from forests and other ecosystems, 35% from agriculture, and 15% from demand‐side measures. The potential varies sixfold across the five regions assessed (0.75–4.8 GtCO2eq yr −1 ) and the top 15 countries account for about 60% of the global potential. Protection of forests and other ecosystems and demand‐side measures present particularly high mitigation efficiency, high provision of co‐benefits, and relatively lower costs. The feasibility assessment suggests that governance, economic investment, and socio‐cultural conditions influence the likelihood that land‐based mitigation potentials are realized. A substantial portion of potential (80%) is in developing countries and LDCs, where feasibility barriers are of greatest concern. Assisting countries to overcome barriers may result in significant quantities of near‐term, low‐cost mitigation while locally achieving important climate adaptation and development benefits. Opportunities among countries vary widely depending on types of land‐based measures available, their potential co‐benefits and risks, and their feasibility. Enhanced investments and country‐specific plans that accommodate this complexity are urgently needed to realize the large global potential from improved land stewardship.

Future carbon emissions from global mangrove forest loss - Maria F. Adame; Rod M. Connolly; Mischa P. Turschwell; Catherine E. Lovelock; Temilola Fatoyinbo; David Lagomasino; Liza A. Goldberg; Jordan Holdorf; Daniel A. Friess; Sigit D. Sasmito; Jonathan Sanderman; Michael Sievers; et al. (Global Change Biology, 2021)
Mangroves have among the highest carbon densities of any tropical forest. These ‘blue carbon’ ecosystems can store large amounts of carbon for long periods, and their protection reduces greenhouse gas emissions and supports climate change mitigation. Incorporating mangroves into Nationally Determined Contributions to the Paris Agreement and their valuation on carbon markets requires predicting how the management of different land‐uses can prevent future greenhouse gas emissions and increase CO 2 sequestration. We integrated comprehensive global datasets for carbon stocks, mangrove distribution, deforestation rates, and land‐use change drivers into a predictive model of mangrove carbon emissions. We project emissions and foregone soil carbon sequestration potential under ‘business as usual’ rates of mangrove loss. Emissions from mangrove loss could reach 2391 Tg CO 2 eq by the end of the century, or 3392 Tg CO 2 eq when considering foregone soil carbon sequestration. The highest emissions were predicted in southeast and south Asia (West Coral Triangle, Sunda Shelf, and the Bay of Bengal) due to conversion to aquaculture or agriculture, followed by the Caribbean (Tropical Northwest Atlantic) due to clearing and erosion, and the Andaman coast (West Myanmar) and north Brazil due to erosion. Together, these six regions accounted for 90% of the total potential CO 2 eq future emissions. Mangrove loss has been slowing, and global emissions could be more than halved if reduced loss rates remain in the future. Notably, the location of global emission hotspots was consistent with every dataset used to calculate deforestation rates or with alternative assumptions about carbon storage and emissions. Our results indicate the regions in need of policy actions to address emissions arising from mangrove loss and the drivers that could be managed to prevent them.

Delayed impact of natural climate solutions - Zhangcai Qin; Bronson Griscom; Yao Huang; Wenping Yuan; Xiuzhi Chen; Wenjie Dong; Tingting Li; Jonathan Sanderman; Pete Smith; Fan Wang; Song Yang (Global Change Biology, 2021)

Nitrate addition stimulates microbial decomposition of organic matter in salt marsh sediments - Ashley N. Bulseco; Anne E. Giblin; Jane Tucker; Anna E. Murphy; Jonathan Sanderman; Kenly Hiller‐Bittrolff; Jennifer L. Bowen (Global Change Biology, 2019)
Salt marshes sequester carbon at rates more than an order of magnitude greater than their terrestrial counterparts, helping to mitigate climate change. As nitrogen loading to coastal waters continues, primarily in the form of nitrate, it is unclear what effect it will have on carbon storage capacity of these highly productive systems. This uncertainty is largely driven by the dual role nitrate can play in biological processes, where it can serve as a nutrient‐stimulating primary production or a thermodynamically favorable electron acceptor fueling heterotrophic metabolism. Here, we used a controlled flow‐through reactor experiment to test the role of nitrate as an electron acceptor, and its effect on organic matter decomposition and the associated microbial community in salt marsh sediments. Organic matter decomposition significantly increased in response to nitrate, even at sediment depths typically considered resistant to decomposition. The use of isotope tracers suggests that this pattern was largely driven by stimulated denitrification. Nitrate addition also significantly altered the microbial community and decreased alpha diversity, selecting for taxa belonging to groups known to reduce nitrate and oxidize more complex forms of organic matter. Fourier Transform‐Infrared Spectroscopy further supported these results, suggesting that nitrate facilitated decomposition of complex organic matter compounds into more bioavailable forms. Taken together, these results suggest the existence of organic matter pools that only become accessible with nitrate and would otherwise remain stabilized in the sediment. The existence of such pools could have important implications for carbon storage, since greater decomposition rates as N loading increases may result in less overall burial of organic‐rich sediment. Given the extent of nitrogen loading along our coastlines, it is imperative that we better understand the resilience of salt marsh systems to nutrient enrichment, especially if we hope to rely on salt marshes, and other blue carbon systems, for long‐term carbon storage.

Pathways of mineral‐associated soil organic matter formation: Integrating the role of plant carbon source, chemistry, and point of entry - Noah W. Sokol; Jonathan Sanderman; Mark A. Bradford (Global Change Biology, 2019)
To predict the behavior of the terrestrial carbon cycle, it is critical to understand the source, formation pathway, and chemical composition of soil organic matter (SOM). There is emerging consensus that slow‐cycling SOM generally consists of relatively low molecular weight organic carbon substrates that enter the mineral soil as dissolved organic matter and associate with mineral surfaces (referred to as “mineral‐associated OM,” or MAOM). However, much debate and contradictory evidence persist around: (a) whether the organic C substrates within the MAOM pool primarily originate from aboveground vs. belowground plant sources and (b) whether C substrates directly sorb to mineral surfaces or undergo microbial transformation prior to their incorporation into MAOM. Here, we attempt to reconcile disparate views on the formation of MAOM by proposing a spatially explicit set of processes that link plant C source with MAOM formation pathway. Specifically, because belowground vs. aboveground sources of plant C enter spatially distinct regions of the mineral soil, we propose that fine‐scale differences in microbial abundance should determine the probability of substrate–microbe vs. substrate–mineral interaction. Thus, formation of MAOM in areas of high microbial density (e.g., the rhizosphere and other microbial hotspots) should primarily occur through an in vivo microbial turnover pathway and favor C substrates that are first biosynthesized with high microbial carbon‐use efficiency prior to incorporation in the MAOM pool. In contrast, in areas of low microbial density (e.g., certain regions of the bulk soil), MAOM formation should primarily occur through the direct sorption of intact or partially oxidized plant compounds to uncolonized mineral surfaces, minimizing the importance of carbon‐use efficiency, and favoring C substrates with strong “sorptive affinity.” Through this framework, we thus describe how the primacy of biotic vs. abiotic controls on MAOM dynamics is not mutually exclusive, but rather spatially dictated. Such an understanding may be integral to more accurately modeling soil organic matter dynamics across different spatial scales.

Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a treeline - Thomas C. Parker; Jonathan Sanderman; Robert D. Holden; Gesche Blume‐Werry; Sofie Sjögersten; David Large; Miguel Castro‐Díaz; Lorna E. Street; Jens‐Arne Subke; Philip A. Wookey (Ecology, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath ( Empetrum nigrum ), shrub ( Betula nana ), and forest ( Betula pubescens ) at a sub‐Arctic treeline in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate‐C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of “labile” C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate C in the tundra.

Variability and Vulnerability of Coastal ‘Blue Carbon’ Stocks: A Case Study from Southeast Australia - Carolyn J. Ewers Lewis; Paul E. Carnell; Jonathan Sanderman; Jeffrey A. Baldock; Peter I. Macreadie (Ecosystems, 2018)

Deciphering sedimentary organic matter sources: Insights from radiocarbon measurements and NMR spectroscopy - Jonathan Sanderman; Evelyn Krull; Thomas Kuhn; Gary Hancock; Janine McGowan; Todd Maddern; Stewart Fallon; Andy Steven (Limnology and Oceanography, 2015)
In a sediment core collected from an estuary in a rapidly urbanizing region in South East Queensland, Australia, we used multiple geochemical tracers to understand the provenance, form, and rate of accumulating organic matter (OM) focusing on the application of two tools often used in studies of soil OM: solid‐state 13 C nuclear magnetic resonance (NMR) spectroscopy and interpretation of radiocarbon ( 14 C) data by modeling the uptake of the bomb‐spike in atmospheric 14 C. While elemental (C, N) and stable isotope ( 13 C, 15 N) data generally could not distinguish OM sources, these data did indicate that there has been a steady increase in nutrient loading to the estuary and that there were periodic deposition events where the OM was dominated by C3 terrestrial vegetation. The NMR results showed that the OM was primarily of terrestrial origin being dominated by lignin and stable char‐like carbon compounds in all samples. The 14 C data and modeling indicated that the OM was composed of a mixture of material with widely varying ages. In general, the OM was hundreds of years older than the age of the sediments as determined by fallout radionuclide dating (1950–2009 chronology), indicating that a large fraction of the OM has resided on the terrestrial landscape for a substantial period before being transported and buried in the estuary sediments. By applying this combination of techniques, we have been able to develop a coherent picture of a very complex deposition and accumulation history in these estuary sediments.

Uncertainty in soil carbon accounting due to unrecognized soil erosion - Jonathan Sanderman; Adrian Chappell (Global Change Biology, 2013)
The movement of soil organic carbon ( SOC ) during erosion and deposition events represents a major perturbation to the terrestrial carbon cycle. Despite the recognized impact soil redistribution can have on the carbon cycle, few major carbon accounting models currently allow for soil mass flux. Here, we modified a commonly used SOC model to include a soil redistribution term and then applied it to scenarios which explore the implications of unrecognized erosion and deposition for SOC accounting. We show that models that assume a static landscape may be calibrated incorrectly as erosion of SOC is hidden within the decay constants. This implicit inclusion of erosion then limits the predictive capacity of these models when applied to sites with different soil redistribution histories. Decay constants were found to be 15–50% slower when an erosion rate of 15 t soil ha −1 yr −1 was explicitly included in the SOC model calibration. Static models cannot account for SOC change resulting from agricultural management practices focused on reducing erosion rates. Without accounting for soil redistribution, a soil sampling scheme which uses a fixed depth to support model development can create large errors in actual and relative changes in SOC stocks. When modest levels of erosion were ignored, the combined uncertainty in carbon sequestration rates was 0.3–1.0 t CO 2 ha −1 yr −1 . This range is similar to expected sequestration rates for many management options aimed at increasing SOC levels. It is evident from these analyses that explicit recognition of soil redistribution is critical to the success of a carbon monitoring or trading scheme which seeks to credit agricultural activities.

Long‐term carbon storage through retention of dissolved aromatic acids by reactive particles in soil - Marc G. Kramer; Jonathan Sanderman; Oliver A. Chadwick; Jon Chorover; Peter M. Vitousek (Global Change Biology, 2012)
Soils retain large quantities of carbon, thereby slowing its return to the atmosphere. The mechanisms governing organic carbon sequestration in soil remain poorly understood, yet are integral to understanding soil‐climate feedbacks. We evaluated the biochemistry of dissolved and solid organic carbon in potential source and sink horizons across a chronosequence of volcanic soils in Hawai'i. The soils are derived from similar basaltic parent material on gently sloping volcanic shield surfaces, support the same vegetation assemblage, and yet exhibit strong shifts in soil mineralogy and soil carbon content as a function of volcanic substrate age. Solid‐state 13 carbon nuclear magnetic resonance spectra indicate that the most persistent mineral‐bound carbon is comprised of partially oxidized aromatic compounds with strong chemical resemblance to dissolved organic matter derived from plant litter. A molecular mixing model indicates that protein, lipid, carbohydrate, and char content decreased whereas oxidized lignin and carboxyl/carbonyl content increased with increasing short‐range order mineral content. When solutions rich in dissolved organic matter were passed through Bw‐horizon mineral cores, aromatic compounds were preferentially sorbed with the greatest retention occurring in horizons containing the greatest amount of short‐range ordered minerals. These minerals are reactive metastable nanocrystals that are most common in volcanic soils, but exist in smaller amounts in nearly all major soil classes. Our results indicate that long‐term carbon storage in short‐range ordered minerals occurs via chemical retention with dissolved aromatic acids derived from plant litter and carried along preferential flow‐paths to deeper B horizons.

The dynamics of soil redistribution and the implications for soil organic carbon accounting in agricultural south‐eastern A ustralia - Adrian Chappell; Jonathan Sanderman; Mark Thomas; Arthur Read; Chris Leslie (Global Change Biology, 2012)
Anthropogenically induced change in soil redistribution plays an important role in the soil organic carbon ( SOC ) budget. Uncertainty of its impact is large because of the dearth of recent soil redistribution estimates concomitant with changing land use and management practices. An Australian national survey used the artificial radionuclide caesium‐137 ( 137 Cs) to estimate net (1950s–1990) soil redistribution. South‐eastern A ustralia showed a median net soil loss of 9.7 t ha −1 yr −1 . We resurveyed the region using the same 137 Cs technique and found a median net (1990–2010) soil gain of 3.9 t ha −1 yr −1 with an interquartile range from −1.6 t ha −1 yr −1 to +10.7 t ha −1 yr −1 . Despite this variation, soil erosion across the region has declined as a likely consequence of the widespread adoption of soil conservation measures over the last ca 30 years. The implication of omitted soil redistribution dynamics in SOC accounting is to increase uncertainty and diminish its accuracy.